Ciclagem de nutrientes por peixes em riachos neotropicais - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
In this study, we evaluated the importance of fish for nutrient cycling in neotropical streams, seeking to identify the main factors determining excretion rates. We approach the cycling of nutrients on an individual and ecosystem scale in different chapters of the thesis and to them we add a chapter in game format in an accessible and playful language to highlight the importance of fish in the cycling of nutrients in streams. We conducted the study in neotropical streams located in and around the Serra dos Pireneus Environmental Protection Area. Thus, we structured the Thesis in three chapters. In CHAPTER I, we tested whether intrinsic (characteristics of individuals) and extrinsic (environmental characteristics) factors can explain the variation in the excretion of fish in streams. We model the excretion of nutrients (per capita and specific mass) in function of intrinsic factors, such as mass, diet of allochthonous invertebrates and phylogenetic kinship, and extrinsic as concentration of nutrients in the environment (N and P), Habitat Physical Integrity Index, Water Quality Index and percentage of natural and anthropic vegetation. Our results showed that the excretion of fish can be particularly influenced by its intrinsic characteristics, especially by the mass of the species and the phylogenetic kinship. In CHAPTER II, we evaluate the contribution of fish to nutrient cycling taking into account the nutrient demand of streams. We have shown that fish contribute significantly to the nutrient cycling of Cerrado streams. This contribution is even more important in more conserved and oligotrophic streams, where fish exceed the demand for nutrients in the environment. Small lambaris (tetras), allochthonous insectivores are dominant in these streams and are responsible for most of the nutrients excreted by the community. In CHAPTER III, we created a game, Fish Pee, in order to promote scientific divulgation through the synthesis of the main results obtained in the previous chapters. We relate different ecological concepts through a playful language and accessible to different audiences.
Nutrients cycling by fish in neotropical Streams
Keywords: Ictiofauna; Parentesco filogenético; Demanda de nutrientes; Divulgação científica; Jogo de tabuleiro; Ichthyofauna; Phylogenetic kinship; Excretion; Nutrient demand; Scientific divulgation; Gameboard; CIENCIAS BIOLOGICAS; CIENCIAS BIOLOGICAS::ECOLOGIA